A rare cause of hyperbilirubinemia in a newborn: bilateral adrenal hematoma - Katar, Selahattin; Öztürkmen-Akay, Hatice; Devecioğlu, Celal; Taşkesen, Mustafa (The Turkish Journal of Pediatrics, 2008)
Hyperbilirubinemia is an important health problem in newborns. The most common causes are Rh and ABO incompatibility, hemolytic anemias, enzyme deficiencies, sepsis, hypothyroidism, pyloric stenosis and breast-milk jaundice. Adrenal hemorrhage is a rare cause of hyperbilirubinemia in the neonate. We present a six-day-old newborn with hyperbilirubinemia and suprarenal hematoma who was born at home without assistance of healthcare personnel. Adrenal hematoma should also be considered in the differential diagnosis of hyperbilirubinemia, particularly in newborns that experienced a difficult delivery.